How to be an inclusive leader : your role in creating cultures of belonging where everyone can thrive - Brown, Jennifer, 1971- (Oakland, CA : Berrett-Koehler Publishers, Inc., 2019)
"Internationally acclaimed diversity and inclusion expert Jennifer Brown shows how we can all shift our perspectives to create a more diverse and inclusive workplace. She breaks down the "us-versus-them" divide that plagues so many diversity initiatives. When people are able to bring their full selves to work and feel welcomed, valued, and respected for their differences, they perform at higher levels and contribute more to their organizations than when they are divided by differences. There is greater trust, cooperation, and community in the workplace, which leads to higher performance and business results. In this brave new book, award-winning entrepreneur and internationally acclaimed diversity and inclusion expert Jennifer Brown offers the best-practice guide for becoming more inclusive in our everyday behaviors and interactions. It shares how we can all shift our perspective to support each other and to develop as allies and even accomplices for workplace inclusion. It also explores how targeting the structural barriers to inclusion at an organizational level is needed to tackle the baked-in inequities of our systems that have persisted and continue to derail inclusion. Through storytelling techniques, the author works to make diversity and inclusion inclusive of everyone. The goal is to help those who have felt irrelevant to diversity and inclusion conversations--or even alienated by them--positively contribute to creating workplaces of greater mutual understanding, compassion, and affirmation that profit from the talents of everyone"--
"We know why diversity is important, but how do we drive real change at work? Diversity and inclusion expert Jennifer Brown provides a step-by-step guide for the personal and emotional journey we must undertake to create an inclusive workplace where everyone can thrive"--
Includes bibliographical references and index.
PB
Keywords: Leadership; Personnel management; Work environment; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Workplace Culture; SOCIAL SCIENCE / Discrimination & Race Relations